THE INACCURACY OF THE PUBLIC PROSECUTOR IN APPLYING THE ARTICLE OF THE CHARGE AS THE BASIS FOR THE JUDGE TO DECIDE ACQUIT - Tsani, Muhammad Saiful (UNISSULA Semarang, 2024)
This study aims to determine and analyze the inaccuracy of the Public Prosecutor (JPU) in applying the indictment article as the basis for the judge to acquit in Decision Number 195/Pid.B/2017/PN.Skg and the correct application of the indictment article as the basis for the judge's decision in Decision Number 195/Pid.B/2017/PN.Skg. This study uses a normative legal approach method, analytical descriptive research specifications. The data used are secondary data with data collection methods including literature studies and documentary studies, while the data analysis method is qualitative. The theory used is the theory of legal certainty and the theory of evidence. Based on the results of the study, it can be concluded that the inaccuracy of the Public Prosecutor in applying the indictment article in Decision Number 195/Pid.B/2017/PN.Skg can be seen in the formulation of the indictment of Article 363 Paragraph (1) Jo Article 56 Paragraph (1) of the Criminal Code, namely the crime of livestock theft, intentionally providing assistance at the time the crime was committed. However, based on the legal facts at trial, there was one element that was not fulfilled. The legal consequence of the prosecutor's carelessness in applying the indictment article was that the judge acquitted the defendant according to Article 182 Paragraph (4) of the Criminal Procedure Code. The correct application of the indictment article as the basis for the judge's decision in Decision Number 195/Pid.B/2017/PN.Skg is the crime of receiving stolen cattle as regulated in Article 480 point 1 of the Criminal Code. This is because based on the legal facts, the defendant only helped sell the stolen cattle and was not directly involved in the theft process, so the defendant's role is more appropriately categorized as a receiver.